Reward management a handbook of remuneration strategy & practice - Armstrong, Michael (Kogan page, 1994)
This third edition of Reward Management, now recognised as the definitive UK text on the subject, has been substantially written to reflect the new thinking and practice that has emerged since the last edition in 1991. Incorporating the results of some highly significant recent UK research, the authors emphasise the strategic importance of reward management as a key contributor to the achievement of sustained competitive advantage.